Accounting for a changing and uncertain climate in planning and policy making today: lessons for developing countries - Ranger, Nicola; Garbett-Shiels, Su-Lin (Climate and Development, 2012)
Climate change is increasingly altering the pattern of climate-related risks. Developing countries and in particular least developed countri es will be among the most severely impacted by climate change. These r isks can seem remote in comparison with more immediate threats and nee ds, but if climate change is not considered upfront in existing planni ng and policymaking processes today, decision makers risk locking-in f uture impacts that may prove irreversible or much more costly and diff icult to rectify than is necessary. The challenge for planners and pol icymakers, explored in this paper, is that future climate conditions a re deeply uncertain. Decision methods are available to tackle these pr oblems; however, these tend to be data- and resource-intensive and the refore, difficult to routinely apply. Further, a gap in currently avai lable guidance is the explicit link to the adaptation needs of a devel oping country. We discuss the implications of this development context for the priorities for adaptation and the relative allocation of effo rts in adaptation. This paper focuses on the identification of adaptat ion options and strategies that are robust to the deep uncertainties i n future climate risk, culminating in a framework of six building bloc ks. It takes the perspective of exploring how decisions today might be adjusted to account for uncertain and changing long-term climate risk s. We suggest a core principle is to focus on promoting climate-resili ent development and increasing long-term adaptive capacity while, cruc ially, avoiding inflexible decisions that could lock-in future climate risk or foreclose adaptation options.
Keywords: Adaptation; Climate change; Development; Planning; robustness; uncertainty